Husserl storico delle idee, fra foreste e ontologie regionali - Serra, Carlo (Bollettino Filosofico, 2024)
Critical History of Ideas is the title Husserl gave to a series of lectures in 1932, focusing on the history of the relationship between truth and perception and to phenomenological reduction. These lectures form the first part of a course dedicated to Erste Philosophie (First Philosophy: Critical History of Ideas and Theory of the Phenomenological Reduction). Their purpose is to reconstruct the genesis of the structural problems of phenomenology through historical perspective. Plato, Descartes, Locke, Hume, and Berkeley are interpreted as opportunities to focus on the fundamental themes of phenomenology. In this sui generis history of ideas, the most substantial section is devoted to the reconstruction of empiricism and its skeptical outcome. This highlights a form of elective affinity between the empiricist world and the phenomenological field, engaging Husserl in remarkable discussions that go far beyond mere historical reconstruction of the genesis of ideas. The underlying intuition of these lectures is that the history of philosophy can be seen as a precursor to philosophical themes, and that there is a common ground of truth between traditions, which must be tested in a typically Platonic dialogic form. Keywords: Acknowledgment, Empiricism, Identity, Immanence, Phenomenological Reduction, Skepticism, Synthesis of Aspects